Pemberdayaan Perempuan dalam Mendaur Ulang Sampah Unorganik di RW 12 Kelurahan Pedurungan Tengah - Firdaus, Firdaus; Nusantara, Agung; Nurhayati, Nurhayati; Nofikasari, Nofikasari; Jatmiko, M.Roby; Nurrahmah, Wa Ode Sitti; Martini, Martini (Jurnal PKM Manajemen Bisnis, 2025)
This community service program, titled "Empowerment of Women in Recycling Inorganic Waste in RT 2, RW 12, Pedurungan Tengah," addresses the urgent need for effective waste management and environmental sustainability. The growing volume of inorganic waste poses significant challenges for local communities, particularly impacting women, who play a vital role in household waste management. The primary objective of this initiative was to empower women by enhancing their skills in recycling inorganic waste while raising awareness about environmental issues. The method employed involved participatory training sessions that included socialization, practical workshops, and group activities focused on recycling techniques. Throughout the program, participants learned to separate, process, and create valuable products from inorganic waste. The results were significant: approximately 80% of the participants demonstrated improved recycling skills and successfully produced marketable items. Additionally, the program fostered a greater sense of community engagement and increased awareness of environmental conservation among residents. In conclusion, this initiative not only empowered women economically but also contributed to a cleaner and more sustainable environment. The program highlights the importance of women as key agents of change in waste management practices, setting a foundation for ongoing environmental initiatives in the community.